Perceived inequality and variability in the expression of parochial altruism - Cody T. Ross; Anne C. Pisor (Evolutionary Human Sciences)
It is commonly argued that humans have generalised predispositions for within-group favouritism and between-group animus (i.e. that humans are parochially altruistic), leading to higher levels of internal conflict in societies with greater diversity. Other research, however, has questioned both the ubiquity of parochial altruism and the role of diversity per se in causing social discord. Here, we use ethnographic, social network and experimental economic game data to explore this topic in two multi-ethnic Colombian communities. We examine the extent to which Afrocolombian and Emberá residents express parochial altruism, finding appreciable variability between communities, and across individuals within communities. When present, parochial altruism appears to be driven by divergent perceptions of group-based economic need, not group identity per se. Our results suggest that diversity may be less likely to cause social discord than past work has suggested, as long as group-based inequalities in wealth, well-being and representation – that can destabilise positive inter-group relationships – are minimised.